Reduced tillage and subsurface fertigation improve productivity and economic benefits in the cotton-wheat cropping system - Singh, Kulvir; Singh, Manpreet; Mishra, Sudhir Kumar; Soufan, Walid; Habib-ur-Rahman, Muhammad; El Sabagh, Ayman (Frontiers in Sustainable Food Systems, 2023)
Soil compaction under repetitive tillage and surface flood method of irrigation (SFMI) are significant hurdles for sustaining crop production in India, necessitating the adoption of efficient soil and water management strategies. Hence, a 3-year field study was conducted at two diverse agro-climatic locations (Abohar and Faridkot) to investigate the impact of subsurface drip (SUSD) fertigation on crop and water productivity of cotton-wheat cropping system (CWCS), over traditional practice (TP) (conventional tillage with SFMI and manual application of nutrients). The experiment was conducted in a factorial randomized complete block design with three levels of subsurface drip irrigation (SUSDI) [100, 80, and 60% of crop evapotranspiration (ETc)] and two fertigation levels [75% recommended dose of nutrients (RDN) and 100% RDN], where TP and surface drip (SD) fertigation at 80% ETc coupled with 100% RDN (Control 2), served as two control treatments. Cotton was raised through reduced tillage, while zero till drill was used for sowing wheat. The results revealed that, barring SUSDI at 60% ETc, both crops exhibited improved yield under all drip combinations of reduced or zero tillage over TP. Better mass and higher length of cotton roots in drip fertigation were evident due to improved steady-state infiltration rates (SSIR) and reduced bulk density (BD) under conservation tillage. When 100% RDN was applied, the 100% and 80% ETc SUSDI resulted in 26.7% and 24.7% higher seed cotton yield (SCY) than TP. Similarly, wheat yield with 100% RDN was improved by 10.5% and 14.4% under SUSDI of 80% and 100% ETc, respectively, over the TP. The results indicated that SUSD can be clubbed with reduced tillage for better soil health, improved crop yield, and higher apparent water productivity. The improved benefit to cost (B:C) owing to enhanced monetary returns over TP also substantiated that reduced tillage with SUSD is a viable and remunerative practice for CWCS. The study elucidated that reduced tillage exercised a beneficial effect on physical soil properties by lowering BD and improving SSIR. At the same time, SUSD could save huge amounts of irrigation water besides enhanced input use efficiency leading to higher crop productivity.